Incidental diagnosis of intra-lobar pulmonary sequestration in an asymptomatic young male: A case report - Prabin Duwadee, MBBS; Suraj Sharma, MD, Radiology; Prabin Kumar Bam, MBBS; Amrit Bhusal, MBBS; Tek Nath Yogi, MBBS; Tilak Khatri, MBBS; Sajiva Aryal, MBBS; Pratick Shrestha, MBBS (Radiology Case Reports)
Bronchopulmonary sequestration is an uncommon abnormality of the respiratory system that often manifests as recurrent pneumonia in childhood or as an incidental discovery on thoracic imaging in adults. The sequestration receives its blood supply from anomalous systemic circulation in contrast to pulmonary circulation and can manifest in either intrapulmonary or extrapulmonary forms. We discuss the instance of a young asymptomatic man who visited us seeking for medical clearance to travel abroad. An opacity was discovered on the chest X-ray, which was followed by a contrast-enhanced CT scan that revealed a well-defined, lobulated soft tissue attenuating lesion in the left lower hemithorax suggesting pulmonary sequestration.